KERJASAMA SISTERCITY DKI JAKARTA - BERLIN DALAM MEMBANGUN TATA KELOLA SMART CITY DI DKI JAKARTA PERIODE TAHUN 2017 - 2020 - Rizki Fitrayansyah, (2023)
This research aims to explain the implementation of sistercity collaboration between DKI Jakarta and Berlin in the effort to develop smart cities in DKI Jakarta in 2017 - 2019. Sistercity cooperation between DKI Jakarta and Berlin has been going on since 1994. In its journey, the collaboration between DKI Jakarta and Berlin focused on developing urban governance and shifted to cooperation in the cultural sector. However, the cooperation between the two cities is more focused on smart city development. Berlin is the proper city for DKI Jakarta to develop smart city governance because it has the same city background. There is a shift in the field of cooperation between DKI Jakarta and Berlin is the reason for the authors to choose this research topic. During the research period, the influence of the development of smart cities from the collaboration of the two cities was felt in the development of smart mobility, smart economy and smart government. The author uses the concept of a sistercity and a smart city as an analysis tool for the implementation of cooperation between these two cities. The method used is qualitative by collecting data through direct interviews with related parties. The results of this study indicate that the implementation of the collaboration that occurred between DKI Jakarta and Berlin in the development of smart cities in DKI Jakarta is very positive for DKI Jakarta itself.